Almost Sure Exponential Stability of Stochastic Differential Delay Equations on Time Scales - Tuan, Le Anh (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: The aim of this paper is to study the almost sure exponential stability of stochastic differential delay equations  on time scales. This work can be considered as a unification and generalization of stochastic difference  and  stochastic  differential  delay equations. Keywords: Delay equation, almost sure exponential stability, Ito formula, Lyapunov function.